Collaborative Governance in Tourism Destination Development from the Initial Condition Dimension in Wajo Regency - Yahya Yahya; Juanda Nawawi; Muh. Tang Abdullah (Journal Social Civilecial, 2025)
This study examines collaborative governance in tourism destination development in Wajo Regency, South Sulawesi, with specific attention to the initial conditions that shape collaboration among stakeholders. Tourism development in Wajo has strong potential through cultural heritage, Bugis identity, silk weaving, Lake Tempe, coastal areas, and rural landscapes. However, this potential has not been fully optimized because of limited institutional capacity, weak coordination, uneven stakeholder participation, and insufficient tourism infrastructure. Using a qualitative descriptive approach, this study collected data through field observations, in-depth interviews, and documentation studies. Informants included officials from the Youth, Sports, Culture, and Tourism Office, Bappelitbangda, technical agencies, tourism business actors, community representatives, and academics. The analysis focused on three dimensions of initial conditions in collaborative governance: the distribution of resources, power, and knowledge; incentives and barriers to participation; and the history of previous cooperation or conflict. The findings show that Wajo Regency has a strong formal foundation for collaboration through planning documents, regional regulations, budget allocation, and cross-sector involvement. Nevertheless, collaboration remains largely government-centered, while community, private sector, and academic participation is still limited and mostly consultative. Incentives for participation exist through investment opportunities, community empowerment, tourism promotion, and academic support, but they are constrained by weak human resources, limited infrastructure, unclear role division, sectoral ego, and uncertain program sustainability. Previous cooperation has occurred through planning forums, cultural activities, promotion programs, Pokdarwis development, and academic partnerships. The study concludes that Wajo needs stronger institutional coordination, substantive participation, capacity building, and sustainable partnership mechanisms to improve tourism governance.